2010
DOI: 10.1051/0004-6361/200913909
|View full text |Cite
|
Sign up to set email alerts
|

C2D Spitzer-IRS spectra of disks around T Tauri stars

Abstract: Context. Dust particles evolve in size and lattice structure in protoplanetary disks, due to coagulation, fragmentation and crystallization, and are radially and vertically mixed in disks due to turbulent diffusion and wind/radiation pressure forces. Aims. This paper aims at determining the mineralogical composition and size distribution of the dust grains in planet forming regions of disks around a statistical sample of 58 T Tauri stars observed with Spitzer/IRS as part of the Cores to Disks (c2d) Legacy Prog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 40 publications
(76 reference statements)
8
59
0
Order By: Relevance
“…Min et al 2008). Additionally, optical properties of large crystalline grains can become degenerate with optical properties of other dust species, since the recognizable emission features of small crystals fade away when increasing s. Limiting s max to 1 μm is in line with previous studies of dust in protoplanetary disks (e.g., Bouwman et al 2008;Juhász et al 2010;Olofsson et al 2010) where crystalline grains are found to be much smaller than amorphous grains. Concerning the maximum grain size for amorphous grains, we tested several values for s max and discuss the outcomes of this exercise in Sect.…”
Section: Absorption Efficienciessupporting
confidence: 80%
See 2 more Smart Citations
“…Min et al 2008). Additionally, optical properties of large crystalline grains can become degenerate with optical properties of other dust species, since the recognizable emission features of small crystals fade away when increasing s. Limiting s max to 1 μm is in line with previous studies of dust in protoplanetary disks (e.g., Bouwman et al 2008;Juhász et al 2010;Olofsson et al 2010) where crystalline grains are found to be much smaller than amorphous grains. Concerning the maximum grain size for amorphous grains, we tested several values for s max and discuss the outcomes of this exercise in Sect.…”
Section: Absorption Efficienciessupporting
confidence: 80%
“…sion features, have been observed numerous times in disks around young Class II objects (e.g., Bouwman et al 2001Bouwman et al , 2008Juhász et al 2010;Oliveira et al 2011;Olofsson et al 2009Olofsson et al , 2010Sargent et al 2009b), and disks around evolved Class III objects (e.g., Beichman et al 2011;Lisse et al 2007Lisse et al , 2008Lisse et al , 2009Weinberger et al 2011). Amorphous grains of olivine (Mg 2x Fe 2(1−x) SiO 4 ) and pyroxene (Mg 2x Fe 2(1−x) Si 2 O 6 ) stoichiometries are also the dominant species in the interstellar medium (∼98%, Kemper et al 2005;Min et al 2007).…”
Section: The Dust Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus that a transition disk geometry does not necessarily go hand in hand Fig. 13. a) Comparison of the mass-averaged sizes of amorphous dust grains as derived from the shorter and longer wavelength part of the IRS spectra (indicated with "W" and "C" superscripts for "warm" and "cold" disk regions) of sources in Cha, MBM 12, η Cha, and the Coronet cluster, and the targets from Olofsson et al (2010). The circles are for the targets in MBM 12, η Cha, and the Coronet cluster.…”
Section: (B) Dust Properties Of Disks Around Cool T Tauri Starsmentioning
confidence: 99%
“…The circles are for the targets in MBM 12, η Cha, and the Coronet cluster. The diamonds show the targets from Olofsson et al (2010). The pentagram marks object ID#10 and 11 in Cha.…”
Section: (B) Dust Properties Of Disks Around Cool T Tauri Starsmentioning
confidence: 99%